Implementation of shared file encrypted storage hierarchical access control scheme - Li LI; Guo-zhen SHI; Xuan WANG; Yun-fei CI (网络与信息安全学报)
The traditional file sharing way is single,lack of security,and the shared file's permission autonomous control is too high.To solve these problems,a file encrypted storage and hierarchical access control scheme was proposed.Through increasing classification management unit in the system,classification of users and documents,users of file access control were achieved,the scope of file access control was realized.Security of file storage and transmission was realized through encryption,the key storage was simplified using hierarchical key.Server file en-cryption and decryption operations were achieved through a special password card,which reduced the server work-load and accelerated the file encryption and decryption processing.The scheme was verified on PC and Zynq plat-form,and the predetermined function was realized.